VARIATION OF SOME TRAITS IN CARROT WITH DIFFERENT ROOT COLORS - A. V. Kornev; V. I. Leunov; A. N. Khovrin (Овощи России, 2017)
The study was carried out in 2008-2016. The field experiments were performed at the territory of breeding centre and experimental facilities of FGBNU All-Russian Research Institute of Vegetable Growing, Moscow oblast. Varieties and hybrids originated from national and foreign breeding programs were used as a plant material for the study. In total 67 accessions including 34 with white root, 27 with yellow root and 6 with violet root were studied. Some traits of carrot were regarded, where it was shown that the root weight (Cv=20.350.5%), the core portion (Cv=10.9-26.7%) and leaf number (Cv=10.8-26.3%) in white carrot were the most variable traits, while a root length (Cv=8.1-15.1%), a leaf length (Cv=7.217.9%) and a root diameter (Cv=6,3-14,1%) were the less variable ones. In yellow carrot the significant variation was revealed in a root weight (Cv=20.1-48.2%), but low variation (Cv=12.2-25.1%) was observed in accession ‘Mestnaya’ from Uzbekistan. The great variation in root weight (Cv=20.152.0%) was found out among purple carrot, but low variation for the trait (Cv=11.1-26.8%) showed the accession ‘Purple Haze’. In the each group of different colored carrots, the hybrid combinations were selected out with low variability in such traits as the root weight, the core portion, the root length.